Cloning, Expression, Isotope Labeling, and Purification of Transmembrane Protein MerF from Mercury Resistant Enterobacter sp. AZ-15 for NMR Studies - Amin, Aatif; Latif, Zakia (Frontiers in Microbiology, 2017)
Mercury resistant (HgR) Enterobacter sp. AZ-15 was isolated from heavy metal polluted industrial wastewater samples near to districts Kasur and Sheikhupura, Pakistan. 16S rDNA ribotyping and phylogentic analysis showed 98% homology with already reported Enterobacter species. The merF gene encoding transmembrane protein-MerF was amplified from genomic DNA and ligated into pET31b+ vector using restriction endonucleases, SphI and XhoI. The genetic codons of merF gene encoding cysteine residues were mutated into codons, translating into serine residues by site-directed mutagenesis. Ketosteroid isomerase (KSI), a fusion tag which is present in pET31b+ vector, was used in the expression of merFm gene. KSI was used to drive the target peptide (MerFm) into inclusion bodies so that the peptide yield and purity were increased. The stable plasmid pET31b+:merFm was transformed into C43(DE3) E.coli cells. The high expression of uniformly 15N isotopically labeled-MerFm protein was induced with 1 mM IPTG. The purification of 15N-MerFm recombinant protein by Ni-NTA and size exclusion chromatography involved an unfolding/refolding procedure. The two-dimensional HSQC NMR spectra of MerFm protein showed the purity and correct number of resonances for each amide. 1H-15N HSQC NMR experiment also confirmed that no modification of the tryptophan residue occurred during cyanogen bromide cleavage. A small scale reservoir of Luria Bertani (LB) medium supplemented with 20 μg/ml of HgCl2 showed 90% detoxification of Hg by Enterobacter sp. AZ-15. The accumulation of Hg on the cell surface of this strain was visualized by scanning electron microscopy (SEM) which confirmed its potential use in Hg-bioremediation.